2015
DOI: 10.1016/j.marpolbul.2015.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and heavy metals in the Grand Bay National Estuarine Reserve in the northern Gulf of Mexico

Abstract: The objectives of this study are to investigate distribution of trace elements and heavy metals in the salt marsh and wetland soil and biogeochemical processes in the Grand Bay National Estuarine Research Reserve of the northern Gulf of Mexico. The results show that Hg, Cd and to some extent, As and Pb have been significantly accumulated in soils. The strongest correlations were found between concentrations of Ni and total organic matter contents. The correlations decreased in the order: Ni > Cr > Sr > Co > Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The Qaidam Basin is one of the vital places of dust storm disasters in China (Gen, 2021), so saline dust storms are a source of HMs that cannot be ignored. Sheng (2015) studied the chemical composition of the Golmud dust storm and revealed that Pb, Zn, Ni, and Cu were gathered in dust aerosols, which anthropogenic emissions may have caused. This paper tested the HM components in atmospheric dustfall (thirty-two samples in total were gathered) in the Qaidam Basin to understand the enrichment and impact of salt-laden dustfall on HMs.…”
Section: Sedimentmentioning
confidence: 99%
“…The Qaidam Basin is one of the vital places of dust storm disasters in China (Gen, 2021), so saline dust storms are a source of HMs that cannot be ignored. Sheng (2015) studied the chemical composition of the Golmud dust storm and revealed that Pb, Zn, Ni, and Cu were gathered in dust aerosols, which anthropogenic emissions may have caused. This paper tested the HM components in atmospheric dustfall (thirty-two samples in total were gathered) in the Qaidam Basin to understand the enrichment and impact of salt-laden dustfall on HMs.…”
Section: Sedimentmentioning
confidence: 99%